Cognitive and Executive Contributions to Trail-Making Task Performance on Adolescents With and Without Attention Deficit Hyperactivity Disorder. Issue 6 (April 2022) - Harvie, Grace; Braund, Taylor A.; Kohn, Michael R.; Korgaonkar, Mayuresh S.; Clarke, Simon; Williams, Leanne M.; Griffiths, Kristi R.
Objective: The trail making task is used to assess executive functioning in ADHD youth, yet has only been validated in adult populations. We compare the relative contributions of various cognitive measures to performance on a trail making task analog, the Switching of Attention (SoA) task, in typically-developing and ADHD adolescents. Method: Participants were 160 adolescents with ADHD from the International Study to Predict Optimized Treatment—in ADHD, assessed at pretreatment baseline and 6-week medicated follow-up, and 160 matched typically-developing peers. Attention, processing speed, working memory, impulsivity, and motor speed were assessed using a cognitive battery. Results: Processing speed and working memory significantly contributed to SoA performance in ADHD, regardless of medication status. While medicated, motor speed also underpinned the prediction of most task measures. For typically-developing adolescents, sustained attention and working memory contributed to SoA performance. Conclusion: Typically-developing, unmedicated and treated ADHD adolescents recruit different aspects of cognition during SoA completion.